Real-World Experience of Safety of Mycophenolate Mofetil in 119 Japanese Patients with Systemic Lupus Erythematosus: A Retrospective Single-Center Study. (25th January 2021) - Abe, Yoshiyuki; Tada, Kurisu; Yamaji, Ken; Tamura, Naoto
Abstract : Objectives . Mycophenolate mofetil (MMF) is the standard treatment for lupus nephritis. In Japan, it was approved for lupus nephritis in 2015. We investigated its real-world safety and effectiveness in Japanese patients with systemic lupus erythematosus (SLE). Methods . We analyzed the continuation rate, adverse events, and reasons for discontinuation of MMF in Japanese patients with SLE in a retrospective single-center study. We included 119 patients who received MMF from 31 July 2015 to 31 May 2019. To compare demographic and clinical characteristics between groups, the Mann–Whitney U -test was used for nonnormally distributed variables. Categorical variables were compared using Fisher's exact test. Kaplan–Meier curves were plotted for the discontinuation rate of MMF. Results . Patients consisted of 18 males and 101 females. Thirty-five patients discontinued MMF. The cumulative discontinuation rate was 42.4%. Twenty-nine patients discontinued MMF due to adverse events, and six patients discontinued MMF due to remission of SLE or desire for childbearing. At the time of the last observation, the lupus low disease activity state achievement rate was significantly lower in patients who experienced adverse events than those who did not (64% vs. 35%, P = 0.009 ). We examined the concentration of mycophenolate acid (trough level) in stored frozen serum in 11 patients. Two patients had irreversible complications due to viral meningitis; their trough mycophenolate acid concentrations were 8.3 and 6.3 μ g/mL, respectively. Conclusions . Although MMF may be effective in Japanese patients with SLE, physicians should pay attention to infections in patients with high mycophenolate acid concentrations.